Adaptive immunity and atherosclerosis: aging at its crossroads - Snijckers, Roy P. M.; Foks, Amanda C. (Frontiers in Immunology, 2024)
Adaptive immunity plays a profound role in atherosclerosis pathogenesis by regulating antigenspecific responses, inflammatory signaling and antibody production. However, as we age, our immune system undergoes a gradual functional decline, a phenomenon termed "immunosenescence". This decline is characterized by a reduction in proliferative naïve B-and T cells, decreased B-and T cell receptor repertoire and a pro-inflammatory senescence associated secretory profile. Furthermore, aging affects germinal center responses and deteriorates secondary lymphoid organ function and structure, leading to impaired T-B cell dynamics and increased autoantibody production. In this review, we will dissect the impact of aging on adaptive immunity and the role played by ageassociated B-and T cells in atherosclerosis pathogenesis, emphasizing the need for interventions that target age-related immune dysfunction to reduce cardiovascular disease risk.